VALIDITY ANALYSIS OF 2A + 2B GRAMMAR - VOCABULARY TESTS AT THE FACULTY OF FRENCH LANGUAGE AND CULTURE, UNIVERSITY OF LANGUAGES AND INTERNATIONAL STUDIES - VIETNAM NATIONAL UNIVERSITY, HANOI - Thuy, Do Thi Bich (VNU Journal of Foreign Studies; Vol 34 No 6DO - 10.25073/2525-2445/vnufs.4326, 2018)
This paper investigated the validity of two grammar - vocabulary tests (2A + 2B proficiency units in the academic year 2016-2017) at the Faculty of French Language and Culture, University of Languages and International Studies - Vietnam National University, Hanoi. The study aimed to evaluate the relevance of the content in these tests in comparison with the test specifications, to measure the difficulty index of each item and some indicators of the tests. The study results showed a relatively high validity of the investigated tests, with a better validity for the second test. However, the language level and items with irrelevant difficulty index should be reviewed to better fit the test specifications.